Unveiling light collection and pump enhancement from quantum wells with plasmonic metasurfaces using power dependent measurements - Mohamed S Abdelkhalik; Aleksandr Vaskin; Toni López; Aimi Abass; Jaime Gómez Rivas (JPhys Photonics, 2023)
Low light extraction efficiency (LEE) is the greatest limiting factor for the brightness of reduced-size light-emitting diodes (LEDs) as it limits their emission intensity. In addition, LEDs have a Lambertian emission, which requires secondary optics to control the emission directionality. Plasmonic metasurfaces can introduce a way of manipulating the generated light from LEDs to enhance their LEE and steer the emitted light by reshaping the far-field emission. Here, we fabricate resonant plasmonic metasurfaces on top of a typical blue emitting wafer consisting of InGaN/gallium nitride quantum wells developed for commercial LED devices. The metasurface is separated from the InGaN quantum wells by p-GaN and indium-tin-oxide (ITO) layers with a cumulative thickness of 110 nm. Since this distance value is close to the emission wavelength in the corresponding medium, enhanced near-fields of localized plasmonic resonances do not reach the active region. Despite this, we observe a strong influence of the metasurfaces on the far-field photoluminescence emission from the quantum wells as demonstrated by Fourier imaging. Power-dependent excitation measurements of the samples allow us to retrieve the pump and light collection enhancement factors provided by the plasmonic metasurfaces. We demonstrate that the plasmonic metasurfaces can provide a pump enhancement factor of up to 4.1 and a collection enhancement factor of up to 3.2. We have also performed simulations based on the reciprocity principle and achieved a good qualitative agreement with the experimental results.